High metastatic node number, not extracapsular spread or N-classification is a node-related prognosticator in transorally-resected, neck-dissected p16-positive oropharynx cancer. Issue 5 (May 2015) - Sinha, Parul; Kallogjeri, Dorina; Gay, Hiram; Thorstad, Wade L.; Lewis, James S.; Chernock, Rebecca; Nussenbaum, Brian; Haughey, Bruce H.
Summary Background Due to unique biology and prognosis, precise identification of predictive parameters is critical for p16+ oropharyngeal squamous cell carcinoma (OPSCC). Prior studies showing absence of prognostication from extracapsular spread (ECS) and/or high N-classification in surgically-treated p16+ OPSCC necessitate new, evidence-based prognosticators. Methods A prospectively assembled cohort of 220, transoral surgery + neck dissection ± adjuvant therapy-treated, p16+ OPSCC patients was analyzed. Disease recurrence and disease-specific survival (DSS) were primary endpoints. Results Median follow-up was 59 (12–189) months. Distribution of metastatic node numbers was: 0 in 9.5% (n = 21), 1 in 33.6% (n = 74), 2 in 17% (n = 38), 3 in 14.5% (n = 32), 4 in 8.2% (n = 18), and <alternatives><inline-graphic xlink:href="ark:/27927/pgjcwgwk9k" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />⩾</alternatives>5 in 17% (n = 37). ECS was recorded in 80% (n = 159), and N2c–N3 in 17% (n = 38). Adjuvant radiotherapy and chemoradiotherapy was administered in 44% and 34%. Recurrence developed in 22 patients (10%); 4 local, 5 regional, 2 regional and distant, and 11 distant. The 3- and 5-year DSS estimates were 94.6% and 93%. Multivariable logistic regression identified <alternatives><inline-graphic xlink:href="ark:/27927/pgjcwgwrbh" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />⩾</alternatives>5 nodes and T3–T4 classification as predictors for recurrence. In multivariable Cox analyses, <alternatives><inline-graphic xlink:href="ark:/27927/pgjcwgwr5x" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />⩾</alternatives>5 nodes, T3–T4 classification and margins were prognostic for DSS. ECS, N2c–N3 classification and smoking were not prognostic. Conclusions Metastatic node number, not ECS or high N-classification is an independent nodal predictor of outcomes in surgically-treated p16+ OPSCC patients. Despite high DSS ( 80%), closer surveillance for recurrence is recommended for patients with <alternatives><inline-graphic xlink:href="ark:/27927/pgjcwgwrgk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />⩾</alternatives>5 metastatic nodes.